2011
DOI: 10.1016/j.ecolecon.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of the possibility of reducing pesticides in French field crops

Abstract: The paper aims to study the effects of reducing pesticide use by farmers in the arable sector in France and the feasibility of a policy target of reducing pesticide use by half. The originality of the approach is to combine statistical data and expert knowledge to describe low-input alternative techniques at the national level. These data are used in a mathematical programming model to simulate the effect on land use, production and farmers' income of achieving different levels of pesticide reduction. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 27 publications
(18 reference statements)
3
60
0
10
Order By: Relevance
“…Modelling has been used to predict the effect of practice changes on economic profits. It showed that with limited changes in terms of farming practices, a reduction of 30 % of the pesticide Treatment Frequency Indicator will not reduce economic profits of farmers in France (Jacquet et al, 2011). Moreover, a prediction showed that the financial investment of sowing wildflower strips adjacent to blueberries was reimbursed from the fourth year after sowing without subsidies (and obviously earlier with subsidies) thanks to the pollination service provided by wild pollinators, but specified that this time frame highly depends on commodity prices (Blaauw and Isaacs, 2014).…”
Section: Economics In the Process Of Changementioning
confidence: 99%
See 1 more Smart Citation
“…Modelling has been used to predict the effect of practice changes on economic profits. It showed that with limited changes in terms of farming practices, a reduction of 30 % of the pesticide Treatment Frequency Indicator will not reduce economic profits of farmers in France (Jacquet et al, 2011). Moreover, a prediction showed that the financial investment of sowing wildflower strips adjacent to blueberries was reimbursed from the fourth year after sowing without subsidies (and obviously earlier with subsidies) thanks to the pollination service provided by wild pollinators, but specified that this time frame highly depends on commodity prices (Blaauw and Isaacs, 2014).…”
Section: Economics In the Process Of Changementioning
confidence: 99%
“…The efficiency of different incentive tools is discussed (e.g. pesticide taxation, quotas of pesticide use, subsidies) (Jacquet et al, 2011;Skevas et al, 2012). In other words, should farmers alone support the costs?…”
Section: Economics In the Process Of Changementioning
confidence: 99%
“…Although the additional costs for farmers are relatively low compared to Norway and Denmark, a use reduction (of AS) is achieved. Even though other measures contributed to this development, the relatively high reduction effects induced by a relatively low tax was confirmed in a simulation study by Jacquet et al [72], in which a 20% reduction is reached by a 16% ad valorem tax.…”
Section: Support Among Farmers Acceptabilitydmentioning
confidence: 68%
“…La méthodologie de la démarche Co-click'eau (Chantre, 2012 ;Chantre et al, 2012) s'appuie sur la méthode de conception de scénarios développée dans le cadre de l'étude Ecophyto R&D (Butault et al, 2010 ;Jacquet et al, 2011). Elle constitue un des outils en appui de la politique nationale de protection des captages vis-à-vis des pollutions diffuses principalement agricoles, politique visant la protection de 500 AAC 3 désignées comme prioritaires dans le contexte du Grenelle de l'environnement.…”
Section: Introductionunclassified